Teacher Agency and Curriculum Reform in Nepalese Mathematics Education: Insights from Currere Narratives - Ghimire, Shurendra (Mathematics Education Forum Chitwan, 2025)
This narrative inquiry examines the subjective, real-life experiences of four secondary mathematics teachers, each possessing over two decades of practice in Nepal, through the conceptual lens of William Pinar’s Currere. Curriculum planning and student-centric reforms in Nepal are structurally centralized around the Tylerian model, which marginalizes teachers as curriculum implementers rather than active developers. This study addresses the critical research gap by using autobiographical reflection to understand how veteran educators interpret and negotiate these centralized reforms. The analysis, structured through the phases of Currere, reveals that the long-practiced reform process has indeed stripped teachers of their role as curriculum researchers. However, the teachers' narratives demonstrate that the challenges they face are intricately intermingled: their emerging professional identities are forged through active struggle against the system’s constraints. They simultaneously navigate profound socioeconomic disparities that undermine student achievement, confront the resultant pedagogical crisis in compulsory math education, and resist the chronic neglect or interference of politics in school governance. These four issues are revealed not as isolated problems but as linked effects of the rigid, objective-based curriculum model. Since this dominant Tylerian approach compromises teacher empowerment, a process-oriented framework like Currere is recommended to foster greater teacher agency and meaningful educational reform in the Nepalese context.